Thermal performance of a microchannel heat sink cooled with carbon nanotube (CNT) nanofluid - Lee, Wei Tong , 1995-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2019